The Effect of the Antiseptic Stimulator Dorogov on the Mammalian Body (Literature Review) - Khasanova Dilnoza Akhrorovna (Genius Journals, 2023)
Studied magazines, materials of scientific conferences, as well as other information sources for the collection of reliable information about the actions of biogenic stimulants on the body of mammals on the example of an antiseptic-stimulant of Dorogov.
Keywords: Biogenic stimulators; tissue therapy; antiseptic-stimulant of Dorogov